The Relationship between Body Mass Index and Degree of Diabetic Retinopathy in Type II Diabetes Mellitus Patients in Mataram Prolanis Community - Arista, Rida; Nasrul, Monalisa; Cholidah, Rifana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Diabetes mellitus is silent killer disease which if it is not treated further, diabetes can cause complications such as diabetic retinopathy. Diabetic retinopathy is the first cause of blindness in productive age. BMI is known to be a risk factor for diabetic retinopathy. Aim of this study was to determine the relationship between BMI and the degree of diabetic retinopathy in type 2 DM patients in the Prolanis Community. The research design uses an observational study with a cross-sectional approach. The sample was type 2 DM patients in Mataram Prolanis Community. Sampling technique used consecutive sampling with minimum sample 29 people. The research results will be analyzed using the Spearman test. Based on the research results, it was found that 46 people had type 2 DM. From 46 people, 7 of them suffered from DR, 5 people had mild NPDR and 2 people had moderate NPDR. From the statistical test results, it was found that there was no relationship between BMI and the degree of diabetic retinopathy with a p value of 0.996 (p > 0.05) and a correlation coefficient of 0.001, which means that the strength of the relationship is very weak between these two variables. The conclusion of the study is that there is no relationship between BMI and the degree of diabetic retinopathy in type 2 DM patients because diabetic retinopathy is a multifactorial disease.